Periodicities in energy dissipation rates in the auroral mesosphere/lower thermosphere - Hall, Chris; Nozawa, S.; Meek, C.E.; Manson, A.H.; Luo, Yi (European Geosciences Union, 2003)
It is possible for medium-frequency (MF) radar systems to estimate kinetic energy dissipation rates by measuring signal fading times. Here, we present approximately 5 years of such results from Tromsø (69° N, 19° E) and in particular, investigate the periodicities present at different altitudes in the regime 80 to 100 km. We detect the known annual variation in the mesosphere and the semiannual variation on the lower thermosphere. In addition, other features are observed including terannual and ~ 27-day components in the lower thermosphere.